Prevention of the Liquoid-Induced Consumption Coagulopathy by the Protease Inhibitor Aprotinin - Müller-Berghaüs, G; Maul, F.-D; Lasch, H.G (Thrombosis and Haemostasis, 1972)
The protease inhibitor aprotinin reduced the incidence of the generalized Shwartzman reaction after Liquoid injection into the rabbit. This inhibitory effect is caused by the interference of aprotinin with the intravascular coagulation process (consumption coagulopathy) since decreases in fibrinogen levels after Liquoid injection were prevented. As the main anticoagulant effect of aprotinin is the inhibition of surface factor activation and as on the other hand Liquoid acts as a surface-active substance, it seems conceivable that aprotinin might prevent Liquoid-induced consumption coagulopathy by interfering with Hageman factor activation.Aprotinin did not have any effect on the incidence of hemorrhages in the lungs in Liquoid-injected animals.Furthermore, aprotinin prolonged the survival time of rabbits injected with Liquoid. This effect is not related to the action of aprotinin on the coagulation process.